2018
DOI: 10.1001/jamanetworkopen.2018.2140
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing–Based Screening for BRCA1/2 Expected Pathogenic Variants Among Adult Biobank Participants

Abstract: Key Points Question Can population-level genomic screening identify those at risk for disease? Findings In this cross-sectional study of an unselected population cohort of 50 726 adults who underwent exome sequencing, pathogenic and likely pathogenic BRCA1 and BRCA2 variants were found in a higher proportion of patients than was previously reported. Meaning Current methods to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
181
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(212 citation statements)
references
References 42 publications
28
181
3
Order By: Relevance
“…The overall prevalence of expected pathogenic BRCA1/2 variants in our population was higher than previous estimates (5,6,13), and may be partly explained by the large number of founder variants detected. The highest prevalence was 1 in 49 (2.1%) in individuals with AJ genetic ancestry, which is similar to the previously established prevalence of 1 in 42 (2.3%) in this population (7,8).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The overall prevalence of expected pathogenic BRCA1/2 variants in our population was higher than previous estimates (5,6,13), and may be partly explained by the large number of founder variants detected. The highest prevalence was 1 in 49 (2.1%) in individuals with AJ genetic ancestry, which is similar to the previously established prevalence of 1 in 42 (2.3%) in this population (7,8).…”
Section: Discussioncontrasting
confidence: 90%
“…As with previous studies, there was a higher rate of relevant cancers in BRCA1 variant positive individuals than in BRCA2, and in women than in men (13,33,34). Over one-third of the variant positive females in our study had a documented current or prior diagnosis of a HBOC-related cancer.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…24 Approximately 0.2% to 0.5% of women carry a pathogenic BRCA variant. 49,50 This varies by population; in Ashkenazi Jewish women up to 2.5% have a pathogenic BRCA variant and 29% to 41% of ovarian cancer is attributed to one of three BRCA founder variants (c.68_69delAG and c.5266dupC in BRCA1 and c.5946delT in BRCA2) compared to 10% in the overall outbred ovarian cancer population. 51 In Iceland, the BRCA2 variant c.999del5 carries an odds ratio (OR) of 20.7 and accounts for 6.0% to 7.9% of ovarian cancer in that country.…”
Section: Brca Genes Brcaness and Methylationmentioning
confidence: 99%
“…Thus, early identification of individuals with a pathogenic variant in BRCA1/2 has the potential to reduce cancer morbidity and mortality in this population. The exact general population prevalence of BRCA pathogenic variants is not known, and has previously been estimated to be approximately 1 in 350 (Drohan, Roche, Cusack, & Hughes, ); however, a recent publication suggested that the general population prevalence might be as high as 1 in 200 (Manickam et al, ). The prevalence among individuals with a personal and/or family history of breast and/or ovarian cancer is higher, and guidelines for BRCA1/2 testing exist (Moyer, ; National Comprehensive Cancer Network (NCCN), ), but these consensus guidelines are constantly changing based on evolving evidence.…”
Section: Introductionmentioning
confidence: 99%